Ontologi Pemikiran TGKH.M. Zainuddin Abdul Madjid tentang Pendidikan Pesantren - Muazzatun Adawiyah (STIS DAFA MATARAM, 2018)
This paper discusses the study of philosophy, namely the ontology of TGKH thinking. M. Zainuddin Abdul Madjid about Islamic boarding school education. Furthermore this study examines the relevance of his educational thinking with education in Indonesia. The research methodology used is descriptive qualitative with a descriptive analysis approach. The results showed that TGKH. M. Zainuddin Abdul Madjid has succeeded in giving his education, guidance and education to the people of Lombok at that time with several concepts and practices, so that the people of Lombok have been able to understand and know about the teachings of Islam.